Los cuasicristales: un premio Nobel a la perseverancia - Argüelles Delgado, Alonso José (2011)
This year’s Nobel Prize in Chemistry was awarded to Prof. Dan Shechtman for the discovery of quasicrystals. Quasicrystals are a kind of crystals which violate someprinciples formulated by the modern science of crystallography,namely because of their aperiodicity. Dan Shechtman proved that this form of matter is different from the common crystals. The discovery of quasicrystals was unexpected and received harsh criticism. Ultimately, experimental data confirmed Shechtman’s hypothesis. Quasicrystals have been extensively studied and their unique properties have been applied successfully in different scenarios.